The Race for a COVID-19 Vaccine: Current Trials, Novel Technologies, and Future Directions. Issue 10 (October 2020) - Brown, Stav; Brown, Tal; Cederna, Paul S.; Rohrich, Rod J.
Abstract : Summary: The Coronavirus Disease 2019 (COVID-19) pandemic has presented a major threat to public health worldwide alongside unprecedented global economic and social implications. In the absence of a "gold standard" treatment, the rapid development of a safe and effective vaccine is considered the most promising way to control the pandemic. In recent years, traditional vaccine technologies have seemed insufficient to provide global protection against the rapid spread of emerging pandemics. Therefore, the establishment of novel approaches that are independent of whole pathogen cultivation, cost-effective, and able to be rapidly developed and produced on a large scale are of paramount importance for global health. This article summarizes the current efforts to develop a COVID-19 vaccine, including the ongoing and future anticipated clinical trials. We also provide plastic and reconstructive surgeons with insight into the novel technologies currently utilized for COVID-19 vaccine development, focusing on the very promising viral-vector-based and gene-based vaccine technologies. Each platform has its own advantages and disadvantages related to its efficacy and ability to induce certain immune responses, manufacturing capacity, and safety for human use. Once the fundamental key challenges have been addressed for viral-vector-based and gene-based vaccines, these novel technologies may become helpful in winning the fight against COVID-19 and transforming the future of health care.